2013
DOI: 10.1111/ejed.12017
|View full text |Cite
|
Sign up to set email alerts
|

OECD Work on Technology and Education: innovative learning environments as an integrating framework

Abstract: IntroductionThe aim of this article is two-fold. First, it presents in succinct summary a selection of the work conducted by OECD in the field of technology and education. This has been an on-going focus since the 1980s and recently, much of this has been carried out under the heading of 'New Millennium Learners'. But the technology focus extends well beyond a single project and includes work on innovation, open educational resources and the development of the digital resources market, as well as ICT use in ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 16 publications
0
50
0
7
Order By: Relevance
“…The Pedagogic Core -Elements and Dynamics (Istance & Kools, 2013, p. 49) It is suggested that a focus on the pedagogic core requires rethinking the spatio-temporal schooling context. This requires an examination of how schools redefine and re-work the notion of learners, educators, content, learning resources, and the dynamics that connect those core elements (Istance & Kools, 2013) (See Fig. 2.).…”
Section: Iles 'Learning Eco-systems' and 'Communities Of Schools'mentioning
confidence: 99%
“…The Pedagogic Core -Elements and Dynamics (Istance & Kools, 2013, p. 49) It is suggested that a focus on the pedagogic core requires rethinking the spatio-temporal schooling context. This requires an examination of how schools redefine and re-work the notion of learners, educators, content, learning resources, and the dynamics that connect those core elements (Istance & Kools, 2013) (See Fig. 2.).…”
Section: Iles 'Learning Eco-systems' and 'Communities Of Schools'mentioning
confidence: 99%
“…Yapılan çalışmalarda öğretmenlere sınıf içi uygulamalarında etkili eğitim öğretim için rehber olmak ve öğrencilerin nasıl ve hangi koşullarda daha iyi öğrenebileceğini tespit etmek amaçlanmaktadır (Istance ve Kools, 2013). Bu amaçla yapılan çalışmalardan biri proje niteliği taşımakta olup, etkili bir fen eğitim ve öğretimi için öğretmenlere yönelik çok sayıda çalıştay içermekte, eğitim ve öğretimin geliştirilmesi için öneriler sunmaktadır.…”
Section: Introductionunclassified
“…Yet the applicability of existing professional learning models is questionable given that wide spread, highly effective use of digital technologies has not been realised (Ertmer & Ottenbreit-Leftwich, 2013;Hammond, 2013;Mama & Hennessy, 2013;Yang, 2012;Zheng et al, 2016). This is complicated by an inappropriate focus on investing in technology without adequate support for teachers to changes their practice (Istance & Kools, 2013). …”
Section: The Implication Of This Variation Is That Teachers May Have mentioning
confidence: 99%
“…Digital technologies in schooling is considered a critical component of global competitiveness (Istance & Kools, 2013).…”
Section: Economic and Global Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation